Data for the Heritage Journal Publication 1760103 - Leventis, Georgios; Kyriakidis, Phaedon; Nikolaidis, Andreas; Kassianidou, Vasiliki; Moutsiou, Theodora; Reepmeyer, Christian; Demesticha, Stella; Akylas, Evangelos; Michailides, Constantine; Zomeni, Zomenia; Bar-Yosef Mayer, Daniella E.; Makovsky, Yizhaq; et al. (My University, 2022)
The data found here are part of the publication HERITAGE 1760103 Phaedon Kyriakidis et al. (2022) Virtual sea-driting experiments between the island of Cyprus and the surrounding mainland in the early prehistroric Eastern Mediterranean Phaedon Kyriakidis, Theodora Moutsiou, Andreas Nikolaidis, Christian Reepmeyer, Georgios Leventis, Stella Demesticha, Evangelos Akylas, Vasiliki Kassianidou, Constantine Michailides, Zomenia Zomeni, Daniella E. Bar-Yosef Mayer, Yizhaq Makovsky, and Carole McCartney
Keywords: SaRoCy; Holocene; Virtual sea-driting experiments; early prehistroric Eastern Mediterranean